1999
DOI: 10.1128/jvi.73.12.10472-10479.1999
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of acis-Acting Mutation in the Capsid-Coding Gene of Moloney Murine Leukemia Virus Extends Its Leukemogenic Properties

Abstract: Inoculation of newborn mice with the retrovirus Moloney murine leukemia virus (MuLV) results in the exclusive development of T lymphomas with gross thymic enlargement. The T-cell leukemogenic property of Moloney MuLV has been mapped to the U3 enhancer region of the viral promoter. However, we now describe a mutant Moloney MuLV which can induce the rapid development of a uniquely broad panel of leukemic cell types. This mutant Moloney MuLV with synonymous differences (MSD1) was obtained by introduction of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The spreading of such SD′ retroelement derived from alternative usage of splice donors is likely to bear consequences on dissemination and pathogenesis of MLV retroviruses. Indeed, we showed in a previous work that inactivation of the SD′ site leads to extensive modifications of MLV leukemogenic properties (Audit et al ., 1999). MLV and other simple oncoretroviruses are implicated in leukemogenic processes through insertional mutagenesis mechanisms, where provirus DNA integrates into the host genome and affects the transcription of the neighbouring genes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The spreading of such SD′ retroelement derived from alternative usage of splice donors is likely to bear consequences on dissemination and pathogenesis of MLV retroviruses. Indeed, we showed in a previous work that inactivation of the SD′ site leads to extensive modifications of MLV leukemogenic properties (Audit et al ., 1999). MLV and other simple oncoretroviruses are implicated in leukemogenic processes through insertional mutagenesis mechanisms, where provirus DNA integrates into the host genome and affects the transcription of the neighbouring genes.…”
Section: Discussionmentioning
confidence: 91%
“…Protein analyses were conducted from cells cultured on 10 cm plates. Extractions of cellular and viral proteins and western blot analysis were performed as previously described (Mougel et al ., 1996; Audit et al ., 1999). Proteins were detected by immunoblotting with a mouse anti‐capsid (p30) monoclonal antibody (H187) (a kind gift from B.Chesebro) used at a 1:300 dilution as the primary antibody and a peroxidase‐conjugated (HRP) goat anti‐mouse antibody (1:2000) as the secondary antibody (Sigma), or with a mouse anti‐matrix (p15) monoclonal antibody (H690) (a kind gift from M.Miyazawa) used at a 1:5 dilution as the primary antibody and an HRP goat anti‐mouse antibody (1:1000) as the secondary antibody (Sigma), or with a rabbit anti‐Pol polyclonal antibody (a kind gift from M.Roth) used at a 1:2000 dilution and an HRP goat anti‐rabbit used at a 1:4000 dilution, or with a rabbit anti‐integrase (p45) polyclonal antibody (a kind gift from F.D.Bushman) used at a 1:2000 dilution as the primary antibody and a peroxidase‐conjugated goat anti‐rabbit antibody (1:2000) as the secondary antibody, or with an anti‐envelope polyclonal antibody, anti‐gp70 of Raüscher (ViroMED) used at a 1:1000 and a peroxidase‐conjugated goat anti‐mouse antibody (1:2000) as the secondary antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vivo revealed that inoculation of a Mo-MLV mutant (MSD1/M1) harboring an inactive SD’ site in newborn Swiss mice changes the MLV leukemogenic properties [ 15 ]. Indeed, whereas WT MLV exclusively induces T lymphoma, the MSD1/M1 mutant can induce a broad panel of leukemia (T lymphoma, erythroleukemia, myelomonocytic leukemia and other leukemia with undetermined origin).…”
Section: Introductionmentioning
confidence: 99%
“…1). SD' mutant viruses replicated more slowly than wild type viruses and they induced altered tumorigenesis in mice (28) (30,31). SD' RNA is specifically incorporated into virions and two viral proteins, P50, which uses the bona fide Gag start codon and P60, which initiates from the CUG codon used by glycoGag and is expressed at lower levels than P50, are encoded by this alternatively spliced RNA (32) (Fig.…”
mentioning
confidence: 99%